Síntese de feromônios de Curculionídeos de interesse econômico - Freitas, Johnnatan Duarte de (2009)
Curculionides are insects that can cause great economic problems toward diverse cultures, for example, the coconut, palm tree, sugarcane, corn, banana and cotton. The agricultural pest control, up to now, uses great amounts of insecticides, which are harmful to the health of flora and fauna, humans and the environment. An ecologically friend, selective and non-toxic alternative to the use of insecticides is the use of pheromones. In this work, we describe the synthesis, in preparative scale, of the following compounds: 5-Nonanol, 2-Methyl-4-octanol, 2-Methyl-4-heptanol, 3-Methyl-4-octanol, 5-Methyl-4-octanol, 4-Methyl-5-nonanol and 6-Methyl-2-hepten-4-ol, the main components of the aggregation pheromone of some insects of the Rhynchophorus and Metamasius genus, both being coconut tree pests. This work also reports the syntheses of 2,8-Dioxa-1-ethyl-3,5,7-trimethylbicyclo[3.2.1.]octane, the main component of the aggregation pheromone of Cosmopolitus sordidus, the main pest of the banana tree culture, of 5-Hydroxy-4-methyl-3-heptanone, the main component of the aggregation pheromone of Sitophilus orysae and Sitophilus zeamais, and of 1-Ethylpropyl-2-methyl-3-hydroxypentanoate, main components of the aggregation pheromone of the Sitophilus granaries. Such insects of the Sitophilus genus are stored grain pests of corn and rice.